Pengembangan Kawasan Permukiman di Wilayah Rawan Banjir Kampung Melayu, Jakarta Timur - Afandi, Aisyah Arimurti; Utama, Vissy Puteri; Khomenie, Apridev; Prabowo, Cindar Hari; Apriyanto, Rio; Barus, Lita Sari; Nurhasana, Renny (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2023)
Structural change and environmental degradation along Ciliwung river resulting in flooding that happened in Kampung Melayu. The flooding events in Kampung Melayu increase the urgency of mitigation-based disaster management implementation. The local government has made several efforts to overcome the problem, including the construction of reservoirs, infiltration systems, canals, and floodgates. This research aims to evaluate the implementation of disaster mitigation in Kampung Melayu and propose new strategies in this area. This research is conducted in data collection and data analysis in order to develop new strategies with the aim to overcome the problems based on the concept of disaster management, adaptive architecture, responsive architecture, and the concept of Disaster Resilient Kampong. This research propose slum upgrading and prevention by providing a livable housing resilient to disaster through residential area development program as a solution to overcome the flooding problems in Kampung Melayu.